Detection and Quantification of Aflatoxins from Commercial Poultry Feed in the Federal Capital Territory, Nigeria - Bridget Maria Jessica Adah; Samuel Mailafia; H O K Olabode; Monday Onapka; James Agbo Ameh; Martha Echioda Ogbole; Odey Odey Ebenezer; Ifeanyi Cajetan Casmir (UMYU Journal of Microbiology Research)
Study’s Excerpt: